Institutional Logics and Relational Inequality in UK Surgery: Demographic Dominance and the Uneven Governance of Careers - Woodhams, Carol; Parnerkar, Ira (Journal of Management Studies, 2026)
Abstract Persistent gender and racial inequalities within elite professions remain inadequately explained by accounts focusing exclusively on either intra‐organizational processes or field‐level institutional dynamics. Relational inequality theory (RIT) provides a powerful account of closure within organizations but offers limited specification of how institutional environments shape variation in inequality outcomes. We bring RIT into dialogue with the institutional logics perspective (ILP), adopting a microfoundational lens to examine how demographic dominance and governance structures jointly shape career inequalities. Using longitudinal data on 3402 junior surgeons across 212 NHS trusts in England, we analyse promotion and exit outcomes across professional subspecialties and employing organizations. Intersectional inequalities are systematically associated with a dominant professional logic as captured by White male density (WMD). Higher WMD amplifies in‐group advantages and out‐group penalties. However, these effects vary across institutional contexts. Professional subspecialties exhibit stronger and more coherent dominance effects, whereas governance‐intensive trusts partially attenuate WMD‐associated advantages, particularly in formalized promotion processes, while exit patterns remain less responsive to governance constraints. In doing so, we clarify how the strength of relational inequality regimes varies systematically across institutional contexts and show that demographic dominance and governance centrality jointly shape when and where intersectional inequalities intensify or recede.